(3CKQ GNJdGa feWi GdJYde GdJTGQci GdeJRGef h ZjQ GdeJRGef Ydi JfejI eaGgje h egGQGJ EfJGL UaMGJ GdEfJQfJ h egGQGJ GdJYGhf h eaghe GdPGJ dOi JdGejP GdMdbI GdGHJOGFjI (B/ s - (3eMeO CMeO YHOGdMejO Cejfs; (3CMeO eMehO aNQi (B: s; (3efGd YHOGdYGd eHGQR (B: s ((3GdbGgQI (B: s (3eMeO CMeO YHOGdMejO Cejf (B: s, 2016)
(3gOa GdHMK GdMGdi Edi bjGS GKQ GNJdGa feWi GdJYde GdJTGQci GdEdcJQhfi GdeJRGef h ZjQ GdeJRGef ai JfejI egGQGJ EfJGL UaMGJ GdEfJQfJ HGSJNOGe HQfGeL (B((3GcSHQjTf hjH(B) (3dOi JdGejP GdMdbI GdGHJOGFjI, h GKQ Pdc Ydi JfejI egGQGJ GdJYGhf h eaghe GdPGJ(B: (3h JchfJ YjfI GdOQGSI ef JdGejP GdUa GdSGOS GdGHJOGFi ef eMGaX GdefjG h JchfJ COhGJ GdHMK ef GNJHGQ eYQai h HWGbI Jbje efJL h ebjGS JYGhf h ebjGS eaghe PGJ(B: (3h NdU GdHMK Edi hLhO GKQ ddJYde GdJTGQci GdEdcJQhfi GdeJRGef h ZjQ GdeJRGef ai JfejI eaGgje h egGQGJ EfJGL UaMGJ GdEfJQfJ h egGQGJ GdJYGhf h eaghe GdPGJ dOi GdJdGejP(B: (3h dcf jhLO GNJdGa ai GdfJGFL dUGdM GdJYde GdJTGQci GdEdcJQhfi GdeJRGefs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddJQHjI (B- (3bSe JcfhdhLjG GdJYdjes
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJYde GdJTGQcis; (3GdJYde GdJTGQci GdeJRGefs; (3GdJYde GdJTGQci ZjQ GdeJRGefs